2016
DOI: 10.1016/j.jcm.2016.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Sonographic Evaluation of a Lower Extremity Angioleiomyoma in a 52-Year-Old Woman

Abstract: Objective: The purpose of this case study is to describe the role of sonographic examination in the initial evaluation of an angioleiomyoma and to discuss the characteristic findings associated with this soft tissue mass. Clinical Features: A 52-year-old woman presented with a large, tender, erythematous mass on the anterolateral aspect of her right knee. Sonographic examination revealed a highly vascular mass within the subcutaneous tissues. Differential considerations included benign soft tissues masses such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 14 publications
0
10
0
2
Order By: Relevance
“…1 It is slowgrowing, generally less than 2 cm in diameter, more common in women, presents in patients ages 10 to 59 years, and most commonly presents on the lower extremities. 1,2 The tumor can be dermal, subcutaneous, or may occur in extraskeletal sites or the superfi cial fascia of the extremities, and produces pain in up to 60% of patients. [2][3][4] The pain often is reported as spasmodic and initiated by light touching, exposure to wind or cold, and other environmental stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 It is slowgrowing, generally less than 2 cm in diameter, more common in women, presents in patients ages 10 to 59 years, and most commonly presents on the lower extremities. 1,2 The tumor can be dermal, subcutaneous, or may occur in extraskeletal sites or the superfi cial fascia of the extremities, and produces pain in up to 60% of patients. [2][3][4] The pain often is reported as spasmodic and initiated by light touching, exposure to wind or cold, and other environmental stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The tumor can be dermal, subcutaneous, or may occur in extraskeletal sites or the superfi cial fascia of the extremities, and produces pain in up to 60% of patients. [2][3][4] The pain often is reported as spasmodic and initiated by light touching, exposure to wind or cold, and other environmental stimuli. 1,5 The pain most patients experience is thought to originate from smooth muscle contraction that produces local ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hirata el al reported that the origin of the angioleiomyoma was not the smooth muscle of an artery but the smooth muscle of a vein because the capsule of the tumor was contiguous with the adventitia of the vessel, which did not contain the internal and external laminae. Moreover, Smith et al reported that a large superficial vein was located in the proximity of an angioleiomyoma, and Mattox et al reported that a large draining vessel was observed inferior to the angioleiomyoma on US. On the basis of these findings, we hypothesize that angioleiomyomas arise from the smooth muscle cells of veins' walls located in the soft tissue in the extremities; therefore, hypoechoic protrusions can be observed on one or both ends.…”
Section: Discussionmentioning
confidence: 99%
“…In ALM, ultrasound examination shows well-defined margins and a homogenous structure, suggestive of benign nature of the lesion [ 8 ]. High resistance in intra-tumor arteries, which suggests the presence of muscular arteries, is the feature of angioleiomyomaon Color Doppler examination [ 9 ]. MRI scan was done in this patient rather than a computed tomography (CT) scan as it shows better resolution and soft tissue differentiation.…”
Section: Discussionmentioning
confidence: 99%